(untitled) (Scottish Archaeological Internet Reports, 2013)
A detailed archaeological description with accompanying illustrations. Excavation identified 270 features and although some were revealed to be agricultural in origin, many formed coherent sites. They included a circular ditched enclosure with later Bronze Age/Iron Age features; two late Bronze Age unenclosed post-built round houses, one with a ring ditch structure within it; three post-alignments and a ditch enclosing a post-setting; two features characteristic of mini souterrains, pits containing ferrous metalworking debris and pits containing Beaker pottery.